Fusion of soft computing techniques in control applications - Koku, A. Buğra. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Sciences and Engineering, 1997., 1997)
The main objective of this thesis work is the formation of an experimental garden, suitable for the demonstration of classical and advanced control concepts, by , an integration of the computational ca.pabilities and the electromechanical equipment that exist in the Mechatronics Laboratory of Boğaziçi University. An equally important and more scholarly objective has been to construct an experiınental platform on which the use of soft computing methodologies in the corıtrol of nonlinear systems can be studied and experimented with and to actually carry out some experimental investigations in this respect.The thesis has both theoretical and experimental constitueııts, on the practical side it details the electromechanical construction of the X-Garden (stands for eXperimental Garden), the development of the software and the experimental designs, whereas the control algorithms designed and implemented using Soft Computing methodologies make up the theoretical side. The software support developed for the X-Garden as a part of this thesis work can be grouped into two. The first group constitutes the C codes written and the second one is on the experimental designs. Both adaptive and non-adaptive fuzzy controllers are studied both by simulations and by real-time implementations.The thesis carries a didactic objective too. It is intended to provide a first reading on fuzzy and fuzzy-neuro control. The fundamental concepts of fuzzy logic are and fuzzy neuro control are therefore explained in detail, in a clear and tractable manner.The thesis, in some parts, intentionally carries the style of a user's manual, this is to ensure that further users of the X-Garden will have no difficulty in experimenting on the platform constnıcted, being able to find clear explanations and instnıctions in this thesis and its appendices on the use of both the mechanical and the software environments.
Keywords: Soft computing.; Fuzzy logic.; Fuzzy sets.